Analisa Kepuasan Sistem Informasi Akademik Mahasiswa Menggunakan E-Servqual - Annisa Putri Rahayu; Heribertus Budi Santoso; Sri Rahayuningsih (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2018)
The student academic information system plays an important role in providing information to students in the form of electronic services. At the Kadiri University The academic information system is still young and not separated from the problem, therefore it is necessary to identify the attributes of the Apasajakah which is assessed still need to be addressed and improved quality of service. Therefore, this research aims to determine the level of user satisfaction as well as attribute E-Servqual Apasajakah whose satisfaction value is low. The E-Servqual dimension is used to identify the attributes that are later examined and asked by respondents. Where the respondents studied were students of semester 4 and 6 of the Kadiri University for 96 students, the number of respondents gained from calculations using Slovin's approach. The result of the distribution of the questionnaire will be in the reliability and validity test, which will then be processed by the method of IPA (Importance Performance Matrix). The results of the research of the number of questionnaire 96 respondents obtained the results of 55 male students and 41 female students, and the 6th semester students with the number of students of 60 students and other 39 students of semester 4 are a number of 36 students. The results of research analysis showed that the satisfaction of SIAKAD users is still low because the average perception (3.13) is less than the average expectation (3.59). Furthermore, the attribute that occupies the Iquadrant is analyzed using the IPA method is the dimensions of fulfilment, responsiveness, reliability, efficiency, and compentation. Sistem Informasi Akademik Mahasiswa mempunyai peranan penting dalam menyediakan informasi kepada mahasiswa dalam bentuk layanan elektronik. Di Universitas Kadiri Sistem Informasi Akademik nya masih tergolong muda dan tak lepas dari permasalahan, oleh karenanya perlu diidentifikasi atribut-atribut apasajakah yang dinilai masih perlu dibenahi dan ditingkatkan lagi kualitas pelayanannya. Maka dari itu penelitian ini bertujuan guna mengetahui tingkat kepuasan pengguna serta atribut E-Servqual apasajakah yang nilai kepuasannya rendah. Dimensi E-Servqual digunakan untuk mengetahui atribut-atribut yang nantinya akan diteliti dan ditanyakan kepada responden. Dimana responden yang diteliti ialah mahasiswa semester 4 dan 6 Universitas Kadiri sejumlah 96 mahasiswa, jumlah responden didapat dari perhitungan menggunakan pendekatan Slovin. Hasil dari penyebaran kuisioner akan di uji reliabilitas dan validitas, yang selanjutnya akan diolah dengan metode IPA (Importance Performance Matrix). Hasil penelitian dari jumlah kuisioner 96 responden didapatkan hasil 55 mahasiswa laki-laki dan 41 mahasiswa perempuan, dan mahasiswa semester 6 yaitu dengan jumlah mahasiswa 60 mahasiswa dan 39 lainnya mahasiswa semester 4 yaitu sejumlah 36 mahasiswa. Hasil analisa penelitian menunjukkan bahwa kepuasan pengguna SIAKAD masih rendah dikarenakan rata-rata persepsi (3,13) lebih kecil dibandingkan dengan rata-rata ekspektasi (3,59). Selanjutnya atribut yang menempati kuadran I setalah dianalisis menggunakan metode IPA ialah dimensi fulfilment, responsiveness, reliability, efficiency, dan compentation.